2019
DOI: 10.24903/bej.v1i1.255
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Student’s Reading Habit in English and Students’ Reading Comprehension Ability

Abstract: Reading comprehension can be influenced by reading habit. This research is intended to identify the students’ ability in reading English. The main objective of this research is to recognize whether there is significant correlation between student’s reading habit in English and students’ reading comprehension ability identified through the use of students’ habit questionnaire and reading test with the text was took from passage in TOEFL test.  These subjects who are involved at this research are second semester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…The finding concerning the partial contribution of genre awareness to reading comprehension confirms the results of the previous studies (e.g. from Andriyani et al, 2019;Azizah & Fahriany, 2017;Grabe, 2012;Hansen, 2018;Kalali & Pishkar, 2015;Karbelaei & Hajezi, 2015;Molotja & Themane, 2018;Nam, 2014;Rozimela, 2014;Sari, 2017;Sawangsamutchai & Rattanavich, 2016;To & Pang, 2019;Xu & Li, 2018;Yayli, 2011). In general, these previous studies led to several findings.…”
Section: Genre Awareness and Reading Comprehensionsupporting
confidence: 89%
See 3 more Smart Citations
“…The finding concerning the partial contribution of genre awareness to reading comprehension confirms the results of the previous studies (e.g. from Andriyani et al, 2019;Azizah & Fahriany, 2017;Grabe, 2012;Hansen, 2018;Kalali & Pishkar, 2015;Karbelaei & Hajezi, 2015;Molotja & Themane, 2018;Nam, 2014;Rozimela, 2014;Sari, 2017;Sawangsamutchai & Rattanavich, 2016;To & Pang, 2019;Xu & Li, 2018;Yayli, 2011). In general, these previous studies led to several findings.…”
Section: Genre Awareness and Reading Comprehensionsupporting
confidence: 89%
“…This finding is supported by Rustania et al ( 2019) who found that there was a positive and significant contribution of the students' reading habits towards their reading comprehension. A similar study conducted by Andriyani et al (2019) showed that there was a significant correlation between reading habits in English and reading comprehension. This finding is supported by Hidayah's (2014) who revealed that both variables were correlated.…”
Section: Reading Habitsmentioning
confidence: 61%
See 2 more Smart Citations
“…At English Department Universitas Jambi, Reading Course or Subject is taught structurally for the first three semesters of academic year namely Reading for General Purposes, Reading for Academic Purposes, and Reading for Professional Contexts, as compulsory and prerequisite subjects at English Department Universitas Jambi. Each reading course has its own specific learning objectives, competences and outcomes to accommodate and facilitate learner's needs in mastering reading comprehension (Andriyani et al, 2019). Since this course is one of prerequisite courses or academic requirements and rules in English Department, the learners must complete a reading course (basic reading) offered at the first semester otherwise they are not allowed to continue or apply reading courses or subjects (advance reading) taught at the second and third semester.…”
Section: Introductionmentioning
confidence: 99%